2016
DOI: 10.1177/1073858416649178
|View full text |Cite
|
Sign up to set email alerts
|

Calpains: Master Regulators of Synaptic Plasticity

Abstract: Although calpain was proposed to participate in synaptic plasticity and learning and memory more than 30 years ago, the mechanisms underlying its activation and the roles of different substrates have remained elusive. Recent findings have provided evidence that the two major calpain isoforms in the brain, calpain-1 and calpain-2, play opposite functions in synaptic plasticity. In particular, while calpain-1 activation is the initial trigger for certain forms of synaptic plasticity, that is, long-term potentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 70 publications
(116 reference statements)
0
44
0
Order By: Relevance
“…Studied intensively as models of learning and memory, the changes in synaptic function that accompany long-term potentiation and long-term depression require rapid, reversible changes in ion fluxes, protein localization and protein phosphorylation, as well as more lasting alterations in transcription and translation. In addition, limited proteolytic cleavage of synaptic proteins such as spectrin, MARCKS, and drebrin by calpains, neutral calcium-activated cysteine proteases, is essential for long-term potentiation involving GluN2B-containing receptors 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Studied intensively as models of learning and memory, the changes in synaptic function that accompany long-term potentiation and long-term depression require rapid, reversible changes in ion fluxes, protein localization and protein phosphorylation, as well as more lasting alterations in transcription and translation. In addition, limited proteolytic cleavage of synaptic proteins such as spectrin, MARCKS, and drebrin by calpains, neutral calcium-activated cysteine proteases, is essential for long-term potentiation involving GluN2B-containing receptors 21 .…”
Section: Introductionmentioning
confidence: 99%
“…For longer forms of memory, calpains may function in synaptic remodeling through proteolytic cleavage of cytoskeletal elements (Briz and Baudry, 2016; Jourdi, 2014). It has also been hypothesized that calpain activity affects dendritic protein synthesis associated with synaptic plasticity (Briz and Baudry, 2016; Briz et al, 2013). In our preceding experiments, although both calpeptin and MDL-28170 are reversible in vivo these inhibitors likely retain some efficacy during the molecular consolidation phase of LFI memory even though the inhibitors were injected prior to training.…”
Section: Resultsmentioning
confidence: 99%
“…At least 14 calpain isoforms and multiple splice variants have been identified in humans (Doshi and Lynch, 2009; Franco and Huttenlocher, 2005; Paquet-Durand et al, 2007; Suzuki et al, 2004; Ueyama et al, 1998; Wu and Lynch, 2006) with calpain-1 and calpain-2 the primary isoforms found in neurons (Baudry and Bi, 2016; Baudry et al, 2013; Briz and Baudry, 2016). Calpain-1 is more sensitive to calcium with in vitro activation occurring at micromolar concentrations while calpain-2 requires near millimolar concentrations of calcium for activation (Baudry and Bi, 2016; Jourdi, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calpains are proteases responsible for the degradation of several cytoskeletal elements (Briz and Baudry 2016) and have been associated with motility and the acrosome reaction (Aoyama et al 2001;Ozaki et al 2001;Ben-Aharon et al 2005), because during capacitation, calpain inhibition blocks motility and the acrosome reaction. We have shown that, by inhibiting spectrin cytoskeleton cleavage via calpain, the normal course of the acrosome reaction is blocked in guinea pig sperm (Bastian et al 2010).…”
Section: Introductionmentioning
confidence: 99%